Kicks Bling Enterprise / Nursyakirah Nizam - Nizam, Nursyakirah (2020)
Kicks Bling is a company that offers washing services and restoring the shoes. Every customer who comes to enjoy the service we offer will definitely come out with a smile. This is because we ensure the best service as if it were like new shoes. We are targeting among adults and teenagers who love the clean and nice shoes. Our service is not limited on any type of shoes and customers can freely decide which parts of shoe they want to be cleaned or restored. The best part is customers could able to see their shoe progress through our website. Kicks Bling is open on every weekdays and weekend except for Sunday and public holidays. Any enquiries regarding to our business, people cam simply visit our website or social media. We chose the famous location for our physical store which is at Jalan Tunku Abd Rahman in Kuala Lumpur. The location is strategic as it surrounded with office buildings and attractions that may attracted more people to come to our store.